PHYLOGENETIC ANALYSIS Pangasionodon hypophthalmus, Pangasius djambal, Pangasionodon gigas, Pangasius sanitwongsei AND HYBRID P. hyphophthalmus X P. djambal - Ibnu Dwi Buwono; Yeni Mulyani; Afa Soraya (Universitas Mataram, 2025)
This study aims to identify the types of striped catfish that have genetic variations and genetic relationships among the test striped catfish. Samples of sutchi catfish (P. hypophthalmus) and hybrid P. hyphophthalmus X P. djambal were obtained from Cijengkol and Subang, West Java. P. djambal from Cirata, P. gigas and P. sanitwongsei from ornamental fish shops in Jakarta. The source of genomic DNA was obtained from small pieces of the combined five caudal fins of each test striped catfish sample. Based on the results of amplification using OPA-2 and OPA-3 primers, genetic variations interpreted with the highest number of polymorphic fragments were found in P. sanitwongsei (3 fragments), P. gigas (2 fragments), hybrid P. hyphophthalmus X P. djambal (2 fragments) and P. djambal (1 fragment), respectively. The results of the NTSYS (Numerical Taxonomy and Multivariate Analysis System) program analysis of the OPA-2 and OPA-3 primer amplicons show that the genetic relationship between P. hyphophthalmus, P. djambal, and the hybrid of P. hyphophthalmus X P. djambal and P. sanitwongsei is relatively close (similarity index 71.30%) based on OPA-2 and 55.9% (based on OPA-3). Otherwise, P. gigas is relatively distant (similarity index 44%) based on the OPA-2 primer and 50% (based on the OPA-3 primer). The OPA-2 and OPA-3 primers can be used to detect polymorphisms of striped catfish species.